Analysis of IFAS and EFAS as Strategic Management for the Development of Kemenkan Banana Chips UMKM Bekasi - Anita Suri; Andini Putri Riandani; Supriyanto Supriyanto; Roni Kristianto; Mutiah Aulia Amali (G-Tech: Jurnal Teknologi Terapan, 2025)
One of the potential industrial sectors is agro-industry. Local agro-industry can enhance the economy of a region by utilizing local resources and local labor. This research aims to identify and formulate strategies for the economic empowerment of small-scale banana chip industries (UMKM Kemekan Indonesia) in Cibarusah District, Bekasi Regency. The research employs qualitative methods, utilizing the Internal Factor Analysis Summary (IFAS) Matrix, External Factor Analysis Summary (EFAS) Matrix, and SWOT analysis to design an appropriate business strategy. Data collection was conducted through direct observation and interviews. The analysis reveals that the strengths of UMKM Kemekan lie in maintaining the quality of raw materials and sustaining market demand, while the opportunities include broader marketing reach through digital technology and social media. However, challenges such as competitive pricing and market expansion persist. Strategies proposed include improving product quality, offering competitive pricing, and leveraging digital platforms to introduce products to both local and foreign markets. These strategies not only aim to enhance product marketing but also contribute to the sustainability of the agro-industry and improve the welfare of local banana farmers.